Knowledge and Perception of Stroke: A Population-Based Survey in Uganda. (6th April 2014) - Nakibuuka, Jane; Sajatovic, Martha; Katabira, Elly; Ddumba, Edward; Byakika-Tusiime, Jayne; Furlan, Anthony J.
Abstract : Purpose . This study, designed to complement a large population survey on prevalence of stroke risk factors, assessed knowledge and perception of stroke and associated factors. Methods . A population survey was conducted in urban Nansana and rural Busukuma, Wakiso district, central Uganda. Adult participants selected by multistage stratified sampling were interviewed about selected aspects of stroke knowledge and perception in a pretested structured questionnaire. Results . There were 1616 participants (71.8% urban; 68.4% female; mean age: 39.6 years ± 15.3). Nearly 3/4 did not know any stroke risk factors and warning signs or recognize the brain as the organ affected. Going to hospital (85.2%) was their most preferred response to a stroke event. Visiting herbalists/traditional healers was preferred by less than 1%. At multivariable logistic regression, good knowledge of stroke warning signs and risk factors was associated with tertiary level of education (OR 4.29, 95% CI 2.13–8.62 and OR 5.96, 95% CI 2.94–12.06), resp.) and self-reported diabetes (OR 1.97, 95% CI 1.18–3.32 and OR 1.84, 95% CI 1.04–3.25), resp.). Conclusion . Knowledge about stroke in Uganda is poor although the planned response to a stroke event was adequate. Educational strategies to increase stroke knowledge are urgently needed as a prelude to developing preventive programmes.